The impact of related party sales by listed Chinese firms on earnings informativeness and analysts forecasts - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2012)
Using a random sample of 140 of China's listed firms, we show an adverse impact of related party (RP) sales of goods and services on the usefulness of accounting earnings to investors and on the quality of earnings forecasts by financial analysts. Consistent with the contention that RP sales may violate the arm's-length assumption of regular transactions and consequently impair the representational faithfulness and verifiability of accounting data, we find that earnings of firms engaged in RP sales are at least 33% less informative after controlling for factors known to affect earnings informativeness. We also find that financial analysts are overly credulous in their acceptance of earnings numbers that are contaminated by unreliable RP sales, and provide less accurate and more optimistic earnings forecasts for firms with more RP sales. Overall, our results provide strong empirical evidence on the negative impact of RP transactions on the usefulness of accounting earnings data used by investors and by financial analysts.